2018
DOI: 10.1038/s41598-018-22364-z
|View full text |Cite
|
Sign up to set email alerts
|

B49, a BST-2-based peptide, inhibits adhesion and growth of breast cancer cells

Abstract: Bone marrow stromal antigen 2 (BST-2) also known as Tetherin has been implicated in the growth and progression of many cancers. BST-2 employs its pro-tumor effects through the formation of BST-2:BST-2 dimers which ultimately promotes cell to cell and cell to matrix adhesion, cell motility, survival, and growth. The aim of this study was to evaluate the effect of a novel BST-2-based peptide—B49 on adhesion and growth of breast cancer cells. Homotypic/heterotypic adhesion, three-dimensional spheroid formation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…We have previously shown that B49Mod1 is a BST-2-based peptide that inhibits cancer cell adhesion [32]. In this study, we show that a cysteine-linked disulfide bond is important for the antiadhesion activity of B49Mod1.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…We have previously shown that B49Mod1 is a BST-2-based peptide that inhibits cancer cell adhesion [32]. In this study, we show that a cysteine-linked disulfide bond is important for the antiadhesion activity of B49Mod1.…”
Section: Discussionmentioning
confidence: 51%
“…It has been previously shown that B49 and B49Mod1 possess anti-adhesion activity [32]. Since B49Mod1 contains cysteine residues that mediate BST-2 dimerization [12][13][14] and the adhesion-promoting function of BST-2 [29], we examined the role of cysteine-linked disulfide (S-S) bonds in the anti-adhesion function of B49Mod1.…”
Section: Cysteine-linked Disulfide Bond Is Important For Anti-adhesiomentioning
confidence: 99%
See 3 more Smart Citations